Histone Acetylation Modifications Affect Tissue-Dependent Expression of Poplar Homologs of C4 Photosynthetic Enzyme Genes - Li, Yuan; Dong, Xiu-Mei; Jin, Feng; Shen, Zhuo; Chao, Qing; Wang, Bai-Chen (Frontiers in Plant Science, 2017)
Histone modifications play important roles in regulating the expression of C4 photosynthetic genes. Given that all enzymes required for the C4 photosynthesis pathway are present in C3 plants, it has been hypothesized that this expression regulatory mechanism has been conserved. However, the relationship between histone modification and the expression of homologues of C4 photosynthetic enzyme genes has not been well determined in C3 plants. In the present study, we cloned nine hybrid poplar (P. simonii×P.nigra) homologues of maize (Zea mays) C4 photosynthetic enzyme genes, carbonic anhydrase (CA), pyruvate orthophosphate dikinase (PPDK), phosphoenolpyruvate carboxykinase (PCK) and phosphoenolpyruvate carboxylase (PEPC), and investigated the correlation between the expression levels of these genes and the levels of promoter histone acetylation modifications in four vegetative tissues. We found that poplar homologues of C4 homologous genes had tissue-dependent expression patterns that were mostly well-correlated with the level of histone acetylation modification (H3K9ac and H4K5ac) determined by chromatin immunoprecipitation (ChIP) assays. Treatment with the histone deacetylase inhibitor trichostatin A (TSA) further confirmed the role of histone acetylation in the regulation of the nine target genes. Collectively, these results suggest that both H3K9ac and H4K5ac positively regulate the tissue-dependent expression pattern of the PsnCAs, PsnPPDKs, PsnPCKs, and PsnPEPCs genes and that this regulatory mechanism seems to be conserved among the C3 and C4 species. Our findings provide new insight that will aid efforts to modify the expression pattern of these homologues of C4 genes to engineer C4 plants from C3 plants.